Rancang Bangun Sistem Transfer Layout PCB Berbasis Arduino Uno R3 - Surya Prasetyo, Adhe; Hasan, Hasan (entries, 2024)
PCB layout transfer system is the process of transferring ink on paper to PCB board to produce component paths. The PCB layout transfer process is an important role in electronic circuit design. The PCB layout transfer process is usually used using an iron that takes a long time. This research is the manufacture of tools that aim to increase efficiency in the process of transferring PCB layoutink transfer process from paper to PCB board which can be set transfer process time with the terms of time set by the user. The results of the PCB layout transfer system research use the Arduino UNO microcontroller , thermocouple temperature sensor, 20 x 4 LCD, DC Motor, L298N Motor Driver, MAX 6675 Driver, Heating Plate, RotaryEncoder , and Relay Module 2 Channel. This system provides an effective semi-automatic solution in the PCB layout transfer process.